Guinea : Poverty Reduction Strategy Paper; Second Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2006)
Guinea's Poverty Reduction Strategy Paper (PRSP) presented well-defined poverty reduction. The government should strengthen capacity to monitor policy and PRS outcomes to facilitate the central role of the PRS as both a policy document and a tool to coordinate policies. Strong macroeconomic policies have to be adopted while ensuring that the composition of expenditure identifies policy weaknesses related to governance and public service delivery, and sets out appropriate policy responses. Linking policies and poverty-reduction strategies to policy targets and outcome indicators is suggested by Executive Directors.